The phytophagous insect community on the Veld Fig, Ficus Burtt-Davyi Hutch - Ross, Sally Jane (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1994)
The quest for patterns in community organisation is a daunting task which may be made easier by concentrating on communities associated with a restricted range of resources and therefore of relative simplicity. Here, the phytophagous insect community on the African fig tree Ficus burtt-davyi Hutch. was studied in an attempt to gain some insight into the factors which influence the composition of insect herbivore communities at a very local level, on individual plants of one host species at a single location. The tree's phenological patterns were detennined, due to their relevance to herbivores, particularly those which are host-specific feeders. The trees exhibited inter-tree asynchrony and intra-tree synchrony in fruit crop initiation, whereas leaf production was synchronous both within and between trees. Sixteen frequently occurring phytophagous insect species fed on the 123 F. burtt-davyi trees in the study area over a period of one year. Factors with the potential to influence the composition of this community were investigated at levels of the whole community (species richness), the guild, and the individual species. At each 'level' the effects of the measured factors on fluctuations in community composition were investigated, both over time (i.e. temporally) and spatially from tree to tree. During the year the phytophage community was influenced largely by temperature, although rainfall and tree phenological changes did exert varying influences on the abundances of guilds and individual species. Tree to tree variation in species richness (and thus commensurately, in the frequencies of occurrence of guilds and individual species) was influenced primarily by tree architectural complexity. Architecturally more complex trees hosted a greater number of species, a relationship largely attributable to effects of passive sampling and within-tree microhabitat heterogeneity and/or the availability of living space. The distributions of the leaf and stem piercing species were strongly associated with the presence of ants and this relationship manifested itself within the community as a whole. The degree of isolation of trees had consequences for individual species and for overall species richness, with the numbers of species present decreasing as trees became more isolated. A detailed analysis of guild distributional patterns revealed that the most important influential factors were those also evident at the level of the whole community and that species within guilds were, on the whole, no more similar to one another with respect to their habitat preferences than species from different guilds. The grouping of species into functional units therefore threw no additional light on the way in which this community is organised. An analysis of possible interspecific interactions between all of the phytophagous species in the community revealed only positive associations, both between species within guilds and between those in different guilds. These were doubtless attributable to autocorrelation as a result of similar habitat preferences. Competition was therefore rejected as an organising force within the community.
Keywords: Phytophagous insects -- South Africa; Phytophagous insects; Insect-plant relationships